Dinâmica populacional de Aegla platensis (Crustacea, Anomura) em um tributário do Rio da Várzea em Frederico Westphalen - RS - Oliveira, Davi de (2009)
This dissertation presents a contribution for the preservation of Aegla platensis, one of the most widely distributed species of anomuran crabs in South America, the only continent where they are found. For this, monthly collections were taken during twelve months, from July/2007 to June/2008, in the Lajeado Bonito (27º 25' 27'' S 53º 24' 39''W), a first order tributary of Rio da Várzea, town of Frederico Westphalen/RS. Specimens were collected by using traps containing lures of bovine liver and a surber sampler with 1 mm mesh. The objectives of the present contribution were: to estimate the population density of A. platensis; to determine the size of males and females in the first maturation; to determine the sex-ratio, the periods of reproduction and recruitment of juveniles; to study the seasonal distribution of the species. This dissertation is divided in three chapters, each one enclosing a pertinent subject to the biology of the A. platensis, in order to provide a more dynamic and objective reading and to facilitate the guiding of articles for publication in scientific magazines of the area. The first chapter deals with the morphologic sexual maturity in A. platensis by studying the changes in the ratios of the corporal dimensions of the animals. For this, 437 males with cephalothoracic length (CL) ranging from 6.00 to 31.75 mm (average 16.11 ± 7.4 mm) and 368 females with CL ranging from 6.08 to 27.92 mm (average 16.07± 6 mm). All the captured specimens were sexed and the following corporeal dimensions were measured: cephalothoracic length (CL) cephalothoracic width (CW), length of right chelipod (RC), length of left chelipod (LC) and height of the larger chelipod (HC). After the register of these measures, the crabs were returned to the stream, to the same place where they were collected. The analysis of morphologic sexual maturity was carried out using the Software Mature 2, considering the measures of CL as independent variables and relating them to the other dimensions, as for males and for females. Based on the relation between the carapace length and the measures of the propod in males and the abdomen width in females, the sexual maturity was esteemed in 19.9 mm of CL for males and 18.2 mm of CL for females. In a second chapter, aspects of the populational dynamics of A. platensis were characterized by studying the sexual ratio, the reproductive period (by the frequency of ovigerous females during the sampling period), the period of recruitment and the average size of males and females. A total of 503 males (180 adults and 323 juveniles), 378 females (169 adults, 187 juveniles and 22 ovigerous) and 76 unsexed juveniles were sampled. CL ranged from 6 mm to 31.75 mm in males, from 6.08 mm to 27.92 mm in females and from 1.39 to 5.98 mm in unsexed juveniles. The average sizes were 16.27 (± 7.35), 16.11 (± 5.95), 4.73 (± 0.96) mm for males, females and juveniles, respectively. The average sexual ratio was 1.33 (± 0.38) male/female. Twenty-two ovigerous females were collected, corresponding to 5.82% of the females captured, being 10 in the winter, 4 in the spring, 7 in the summer and 1 in the autumn. The size of these females varied from 16.7 to 24.87 mm CL. The presence of juveniles was verified in all seasons, more frequently in the summer. In the third chapter, we evaluated the spatial and temporal distribution of A. platensis. Besides morphometric data, physical-chemical parameters were also registered, as pH, dissolved oxygen, temperature of the water, electric conductivity, pluviosityl and water outflow. The sediment of each sampling site was characterized according to the size of the particles composing it. A total of 957 specimens was sampled using a surber sampler and traps made of pet bottles in a stretch of 150 meters throughout the stream. Of the total of individuals collected, 200 were sampled in winter (20.90%), 255 in spring (26.65%), 219 in summer (22.88%) and 283 in autumn (29.57%). The population density was calculated by the Petersen s method. The density of individuals/m2 was 3.83 in winter, 1.8 in spring, 3.29 in summer and 2.33 in autumn. The values of temperature of the water, pH, conductivity and dissolved oxygen were statistically similar between the seasons of the year. No relation was found between the physical chemical parameters of the water and the abundance of eglids. The average number of individuals collected varied throughout the seasons (p<0.05). Adult females presented negative correlation with rocks between 6 and 12 cm of diameter (P<0.01) and the number of juveniles increased with quantity of leaves in the substratum (p<0,05).